2020
DOI: 10.1088/1742-6596/1618/3/032009
|View full text |Cite
|
Sign up to set email alerts
|

Simplified approach for the optimal number of rotors and support structure design of a multi rotor wind turbine system

Abstract: In this study different multi rotor wind turbine systems (MRSs) are designed in such a way that the space frame, forming the connection between rotor nacelle assemblies (RNAs) and tower, will be modeled and dimensioned as an ideal truss work. The main focus is on multi digit MRSs (MD-MRS) with a high number of rotors. To dimension the tube diameters and wall thicknesses, a simplified load case is used with an adjusted safety factor for loads. Parameters that are varied are the number of rotors, depth of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The MRS and the 20 MW single rotor turbines are scaled and based on the 10 MW DTU reference turbine [15]. The design is based on concept studies done in [16] and [17] and is shown in Figure 1. Figure 2 shows the numbering of the rotors and the position of the yaw bearing.…”
Section: Mrs Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The MRS and the 20 MW single rotor turbines are scaled and based on the 10 MW DTU reference turbine [15]. The design is based on concept studies done in [16] and [17] and is shown in Figure 1. Figure 2 shows the numbering of the rotors and the position of the yaw bearing.…”
Section: Mrs Simulation Modelmentioning
confidence: 99%
“…Figure 2 shows the numbering of the rotors and the position of the yaw bearing. In [16] and [17] different concepts for the yaw bearing of an MRS are shown, whereby the twin-bearing approach with fixed and floating bearing was considered. The modelling of such a twin-bearing in Bladed is not possible at the moment, which is why a central yaw bearing is assumed for both simulations.…”
Section: Mrs Simulation Modelmentioning
confidence: 99%